The Effect of Using Blogger on Improving the Argumentative Writing Skills of 11th-Grade Students at Jerisa Mandiri Private Vocational High School in Medan - Elena Damayanti Sihotang; Juni Agus Simaremare; Vina Merina Br Sianipar (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This study aims to determine students’ argumentative writing skills before and after the use of Blogger media and to examine its effect on improving those skills. The research employed a quantitative approach with an experimental method using a one group pretest and posttest design. The sample consisted of 30 students of a vocational high school in Medan. Data were collected through tests, observation, and documentation. Data analysis used descriptive and inferential statistics, including normality test, homogeneity test, and hypothesis testing using paired sample t test. The results showed that the mean score increased from 57.20 to 77.87 with an improvement of 20.67 points. The data were normally distributed and homogeneous. The hypothesis test indicated a significance value lower than 0.05, which means that the use of Blogger media had a significant effect on improving students’ argumentative writing skills. Therefore, Blogger media is effective in teaching argumentative writing.